Fatty acid profile, color and lipid oxidation of organic fermented sausage during chilling storage as influenced by acid whey and probiotic strains addition (Scientia Agricola, 2015)
Organic fermented sausages typically spoil during long-term storage due to oxidative rancidity. The application of natural antioxidants to meat stuffing is a major practice intended to inhibit the oxidation process and color changes. This study aimed to assess the effect of two unusual starter cultures: three probiotic strains (Lactobacillus casei LOCK 0900, Lactobacillus casei LOCK 0908 and Lactobacillus paracasei LOCK 0919) and lactic acid bacteria from acid whey on model fermented sausage type products focusing on oxidative stability by measuring instrumental color (L*, a*, b* values), conjugated dienes (CD), TBARS immediately after 21 days of ripening (0) and after 90 and 180 days of refrigerated storage (4 ºC). Determination of fatty acid composition, in meat product was performed after ripening and after 180 days of storage. At the end of the storage period, the salted sausages were characterized by the same content of polyunsaturated fatty acids (PUFA) compared to cured samples. The addition of acid whey and a mixture of probiotic strains to nitrite-free sausage formulation was barely able to protect lipids against oxidation in comparison to nitrite during vacuum storage. Surprisingly, the use of acid whey has an influence on the desired red-pinkish color of organic fermented sausage after ripening and after 180 days of storage period.